FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA KARYAWAN DI KANTOR KEMENTRIAN AGAMA KOTA DUMAI - Fitri, Rahmi Pramulia; Nurlaili, Nurlaili; Suryani, Suryani; Asnel, Roza (Universitas Batam, 2021)
Job stress is defined as a situation in the form of pressure or demands faced by individuals in their work so that they can cause psychological or physical problems. Workload, age, years of service, sex are the factors that cause work stress. Based on a preliminary survey that was conducted at Kantor Kementrian Agama Kota Dumai about the work stress of 6 employees, 4 people experienced work stress and 2 people did not experience work stress. This purpose is to determine the factors associated with job stress. This type of research is a quantitative study using a cross sectional approach. This research was conducted at Kantor Kementrian Agama Kota Dumai with a population of 53 respondents and all respondents were sampled. The research measurement tool is a questionnaire. Then univariate and bivariate analyzed using the chi square test. The results showed that the factors related to work stress were workload (P value = 0,049 < 0,05), gender (P value = 0,028 < 0,05). Meanwhile, those that are not related to work stress are years of service and age. The conclusion of.this.study is that the factors associated with work stress are workload and gender. It.is.recommended to employees to reduce excessive workload.